Identification of A1286C Methylenetetrahydrofolate Reductase Gene Polymorphism in Orbital Region Basal Cell Carcinoma Patients - Anisah Khairunnisa; Ibrahim Ibrahim (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: The development of basal cell carcinoma (BCC) shows variations among individuals. The risk factor for development of BCC related to environtmental factor especially exposure to ultraviolet radiation and individual factor. The one of internal risk factor contribute to basal cell carcinoma developmental is genetic instability include defects in folic acid synthesis or DNA synthesis. The critical enzim that participate in the process is regulated by Methylenetetrahydrofolate Reductase (MTHFR) gene. Method: This study was descriptive observational with case study involved 10 orbital region basal cell carcinoma. The diagnosis was based on histopathologic examination of the tumor. Genotype frequencies of A1286C polymorphism were studied by Polymerase Chain Reaction (PCR), amplification and restriction fragment length polymorphism analyses using MboII enzyme. Result: In the present study, from 10 subjects we found male was 7 people (70%) and female was 3 people (30%). Majority of subjects have history of having a job in the sunlight. The most commont of the BCC is nodular (80%). There is one subject with recurrent case. Analysis result of A1286C MTHFR gene show wild type in all cases. Conclusion: There’s no A1286C substitution methylenetetrahydrofolate reductase gene were identified. The whole subjects are wild type.Keywords: basal cell carcinoma, orbital region, folic acid, polymorphism, A1286C MTHFR gene, polymerase chain reaction (PCR), wild type